Understanding The Influence Of Emotional Intelligence On Organizational Commitment - Khalili, Ashkan (2011)
Emotional intelligence (EI) has become a familiar issue between educators, counselors and business leaders. However this field makes a chance for proving emotional intelligence\'s development and effectiveness as well as opening many opportunities for research. The effectiveness of emotional intelligence was tested among 142 employees from LAR Consulting Engineers (LCE) company which is small and medium enterprise (SME) in private sector in Iran.